The role of the Africentric worldview in the Liberatory process - Hill, Brian J. (Frontiers in Sociology, 2023)
As the Black Lives Matter movement brings increasing awareness to systemic racism in American society, the Eurocentric worldview and intellectual racism nonetheless remain prevalent. However, opportunity to engage with Africentric knowledge that could help counter the focus on Eurocentric worldview among adults remains limited in graduate courses. When such opportunities do arise, however, they are powerful and transformative. This paper conducts a case study of four students of African descent enrolled in graduate programs that engaged with Africentric knowledge. The results demonstrate that such experiences can create a powerful Liberatory transformation. The five step Liberatory process is a cognitive awakening and a discussion of the implications for practice and research are presented as well.